2021
DOI: 10.25008/bcsee.v2i1.1144
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Electronic Medical Records System EQUALI to Improve Patient Care

Abstract: In the present, where we live a pandemic because of Covid-19, it presents a challenge and change in the way we live for all, in which a different way of being able to receive health care must be created. in this research aimed to implement the electronic medical records system to improve patient care, such research is descriptive-explanatory in which a population of 67 patients from a health center is sampled. In conclusion, the implementation of the Electronic Medical Records System improved patient administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Similarly, the influence exerted by EHR on the dimensions reliability, responsiveness, safety, empathy and tangible aspects of care was verified, taking into account that p-value<0.05. These results are similar to those of Cotrina (14) whose study evaluated the implementation of an electronic medical records system to improve patient care. In this regard, the author found that the implementation of the EHR system directly affects the level of patient satisfaction, considering the time of care and the responses obtained.…”
Section: Descriptive Analysissupporting
confidence: 81%
See 1 more Smart Citation
“…Similarly, the influence exerted by EHR on the dimensions reliability, responsiveness, safety, empathy and tangible aspects of care was verified, taking into account that p-value<0.05. These results are similar to those of Cotrina (14) whose study evaluated the implementation of an electronic medical records system to improve patient care. In this regard, the author found that the implementation of the EHR system directly affects the level of patient satisfaction, considering the time of care and the responses obtained.…”
Section: Descriptive Analysissupporting
confidence: 81%
“…Similarly, Cotrina's study focused on evaluating the adoption of an electronic medical records system to improve patient care at the San Miguel Health Center in Peru. (14) study focused on evaluating the adoption of an electronic medical records system to improve patient care at the San Miguel health center in Peru. As a result, with the use of the proposed application, patient satisfaction in terms of time of care at the health center reached a level of 61%, which represents an improvement of 17% compared to the initial situation, where satisfaction stood at 44%.…”
Section: Introductionmentioning
confidence: 99%
“…Collecting data by collecting literature, journals and readings related to research [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21].…”
Section: ) Data Collection Methodsmentioning
confidence: 99%
“…The process of finding Sudoku answers using the BFS is as follows [4], [7], [22], [41], [42]: 1) Search starts from an empty root node 2) From this root node, all possible numbers that can be entered in box-0 are developed without violating the Sudoku rules. Each of these possible numbers is entered into a single node at level-0.…”
Section: Bfs To Complete Sudoku Gamementioning
confidence: 99%
“…Distance tele-education is a didactic training used for student training that promotes synchronous, participatory communication, but there were many inconveniences for students, teachers in the teaching syllabi, particularly at the beginning of its use, causing inconvenience (Cotrina Aliaga et al, 2021). In the midst of the pandemic, Espinoza-Cordero et al, (2021)access to educational technology is limited, causing students to struggle with their work and experience connectivity issues. As a result, educational quality suffered and students suffered.…”
Section: Introductionmentioning
confidence: 99%